Gastric phytobezoar presenting one week after an uneventful robotic hiatal hernia repair: a case of successful dissolution with Coca-Cola beverage - Quang, Camille Mai-Phuong Tran; Alla, Mrinalini; Marfo, Nana; Bodden, Chloe; Louis, Martine A. (International Surgery Journal, 2025)
Bezoars are conglomerates of undigested foreign material that are not commonly found in the stomach or intestines. Although there are different classifications of bezoars, 40% are due to phytobezoars which are made of indigestible fibers. Predisposing factors such as gastric surgery, medication or other medical conditions may aid in the development of bezoars. Here we describe a case of a gastric phytobezoar in a patient just one week after a robotic hiatal hernia repair, successfully treated by chemical dissolution using Coca-Cola. The patient was admitted to the surgical services with nasogastric decompression, intravenous resuscitation and antibiotics after an abdominal-pelvic computed tomography demonstrated a large amount of food in the stomach. Subsequent kidneys, ureters, and bladder (KUB) images showed a persistent large amount of retained food, and the patient underwent an Esophagogastroduodenoscopy (EGD) on day 3 of admission. Coca-Cola was infused on day 5 and day 6 of admission and the subsequent KUB showed improved gastric distension. Patient underwent another EGD on day 7 of admission which revealed an empty stomach. She was then advanced to a full liquid diet, had a bowel movement and was discharged on day 8 of admission. Bezoars are conglomerates of undigested material with gastric surgery being cited as the most common risk factor. However, it is not commonly found after a hiatal hernia repair. Chemical dissolution with Coca-Cola is a successful non-invasive alternative to the surgical removal of the phytobezoar.